The nanocrystalline cellulose from Ananas comosus leaf wastes: An overview to extraction, purification, and applications as curcumin drug delivery system - Sumaiyah Sumaiyah, Poppy Anjelisa Zaitun Hasibuan, Hafid Syahputra, Muhammad Fauzan Lubis (Journal of Applied Pharmaceutical Science, 2024)
Currently, antibacterial materials are attracting considerable attention across various fields. In this study, curcumin (Cur) was prepared with nanocrystal cellulose (NCC) into the polyvinyl alcohol (PVA) matrix to improve the functional properties of a pure Cur-NCC-PVA film. The NCC was obtained from Ananas comosus leaves and characterized by Fourier transform infrared (FTIR), scanning electron microscope (SEM), X-ray diffraction (XRD), and particle size analysis. The variations of Cur concentrations (50, 75, and 100 μg) were added to prepare Cur-NCC-PVA films. The release kinetics of Cur from the films was determined using a spectrophotometer and the release kinetic model was obtained using Korsmeyer-Peppas kinetic model. The antibacterial activity of Cur-NCC-PVA films was established using the diffusion method. The results of NCC characteristics showed satisfactory significance. The FTIR showed a functional group of chemical composition that confirmed the removal of non-cellulosic constituents. XRD confirmed the crystallinity index of NCC of 75.89%. Meanwhile, the particle size of NCC of 268.45 nm. The development of Cur-NCC-PVA films showed a uniform yellow color. The release of curcumin in all films was increased depending on the time following the zero-order kinetic reaction. The non-Fickian kinetics demonstrated the mechanism of Cur release from the film. The Cur-NCC-PVA films in Cur concentration of 100 μg were confirmed to have the highest antibacterial activity and significantly different between 50 and 75 μg Cur-NCC-PVA films against Bacillus subtilis, Streptococcus spp., and Escherichia coli. The Cur-NCC-PVA films described the potential activity for topical formulation in skin disease treatment.
Keywords: Ananas comosus, nanocrystall cellulose, curcumin, non-Fickian, antimicrobial activity